2016
DOI: 10.1159/000444395
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Anti-VEGF Agents on Intraocular Pressure in Age-Related Macular Degeneration

Abstract: Purpose: To analyze the effect of anti-vascular endothelial growth factor (VEGF) agents on intraocular pressure (IOP) in patients with neovascular age-related macular degeneration (AMD). Materials andMethods: This is a retrospective study that included 72 patients treated unilaterally with anti-VEGF agents according to a pro re nata regimen. Fellow noninjected eyes (n = 72) were used as controls. IOP variation and the development of sustained ocular hypertension (OHT) were assessed both in the injected and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In this regard, and based on data collected from the study population, no noteworthy safety risks for patients receiving a minimum of 3 doses during the 6-month period (as per the protocol) were identified. These results were consistent with those of previous studies (11,(14)(15)(16)(17)(18)(19)23,(28)(29)(30)(31), further confirming that bevacizumab has a favorable safety profile for its use in nAMD. None of the serious (or severe) systemic AEs that may be associated with the parenteral administration of anti-VEGF drugs were observed (14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, and based on data collected from the study population, no noteworthy safety risks for patients receiving a minimum of 3 doses during the 6-month period (as per the protocol) were identified. These results were consistent with those of previous studies (11,(14)(15)(16)(17)(18)(19)23,(28)(29)(30)(31), further confirming that bevacizumab has a favorable safety profile for its use in nAMD. None of the serious (or severe) systemic AEs that may be associated with the parenteral administration of anti-VEGF drugs were observed (14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…Risk factors for chronic ocular hypertension in these studies are intuitive. The total number of injections was demonstrated to be a risk factor, 11,40,48,49,93,99 as was a greater frequency of injections 79 and a pre-existing diagnosis of glaucoma prior to initiation of IVIs. 22,40 Fruend et al observed that ranibizumab, as compared to aflibercept, had higher rates of ocular hypertension, with 8.4% of patients on monthly ranibizumab having an IOP of greater than 21mmHg on two consecutive visits compared to 3.2% and 2.7% of patients who received 2 mg and 0.5 mg of aflibercept every month, respectively.…”
Section: Long-term Effects Of Intravitreal Anti-vegf Injections mentioning
confidence: 99%
“…A report from the IRIS (Intelligent Research in Sight) Registry revealed a clinically and statistically significant sustained IOP rise overall and specifically in eyes receiving bevacizumab or ranibizumab, but not in eyes that received aflibercept [ 11 ]. The overall findings of the registry have been backed by multiple smaller studies [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%